Study of the Economic Efficiency of Secondary Olive Waste in the Production of Compost in Lattakia Governorate - احسينه علي (Latakia University Journal -Biological Sciences Series, 2025)
This study constitutes an important contribution to benefit from unused economic resources, in a way that adds positive value to investment opportunities, which in turn increases income at the individual level, as well as at the national level through the added value of the agricultural sector, and the savings in foreign exchange on alternative imports. Therefore, this research aimed to study the economic efficiency of secondary olive waste in compost production. The descriptive analytical approach was adopted to describe the reality of secondary olive waste in Lattakia Governorate, and to monitor quantitative data through primary data represented by three research forms directed to olive farmers in Lattakia Governorate, in addition to secondary data collected through references and statistics available at the Ministry of Agriculture and Agrarian Reform, and the Arab Center for the Studies of Arid Zones and Dry Lands (ACSAD). When comparing the economic efficiency indicators of olive oil production for the sample of producers, it was found that the use of compost led to higher efficiency than not using it in the production process. Likewise, the economic efficiency indicators of using compost fertilizer in the control sample were higher than not using it.